A reprogrammable multifunctional chalcogenide guided-wave lens. Issue 36 (5th June 2018) - Cao, Tun; Wei, Chen-Wei; Cen, Meng-Jia; Guo, Bao; Kim, Yong-June; Zhang, Shuang; Qiu, Cheng-Wei
Abstract : An ultrafast reconfigurable and reprogrammable 3D transformation optics device made of chalcogenide glass with a refractive index gradient. Abstract : The transformation optics (TO) technique, which establishes an equivalence between a curved space and a spatial distribution of inhomogeneous constitutive parameters, has enabled an extraordinary paradigm for manipulating wave propagation. However, extreme constitutive parameters, as well as a static nature, inherently limit the simultaneous achievement of broadband performance, ultrafast reconfigurability and versatile reprogrammable functions. Here, we integrate the TO technique with an active phase-change chalcogenide to achieve a reconfigurable multi-mode guided-wave lens. The lens is made of a Rinehart-shaped curved waveguide with an effective refractive index gradient profile through partially crystallizing Ge2 Sb2 Te5 . Upon changing the bias time of the external voltage imparted to the Ge2 Sb2 Te5 segments, the refractive index gradient profile can be tuned with a transformative platform for various functions for visible light. The electrically reprogrammable multi-mode guided-wave lens is capable of dynamically acquiring various functionalities with an ultrafast response time. Our findings may offer a significant step forward by providing a universal method to obtain ultrafast and highly versatile guided-wave manipulation, such as in Einstein rings, cloaking, Maxwell fish-eye lenses and Luneburg lenses.